A Role of Early Life Stress on Subsequent Brain and Behavioral Development - Damien A. Fair; Alice M. Graham; Brian Mills (Washington University Journal of Law & Policy, 2018)
The prevalence of pediatric neuropsychiatric disorders has risen dramatically during the past two decades. A study surveying the years 1997-2008 verified that one in six children have a developmental disability – a number on the rise. Along similar lines, studies show higher incidents of criminal activity, substance use disorders, and the emergence of psychopathologies in early adolescence and young adulthood, which are particularly sensitive periods of brain and behavioral maturation. While developmental trajectories that may lead to adverse outcomes in youth are the result of a mix of genetics and environmental exposure, it is becoming clearer that they do not start at the time of the diagnosis or problem behaviors; rather, these developmental trajectories start at the earliest periods of life. The ability of children to achieve their full physical, academic, and social potential is tightly related to early life events, some of which may occur even before birth. The science is now amassed with investigators and research targeting the role of Early Life Stress and its interaction with biological systems in impacting the development of the brain and complex behaviors across all stages of development.
Keywords: developmental neuropsychiatric disorders; brain development; genetics; Early Life Stress; ELS; treatment; prevention; juvenile justice system; substance use; psychopathologies; mental health; developmental programming